Dishwashing Soap Making Training and Promotion to Improve Household Economy in Medan Krio Village - SINAGA, Anisa Paujiah; MELATI, Melati; KHAIRUNNISA, Salsabillah Zahwa; MIERA, Zahra Fatin; AISYAH, Siti (PT Keberlanjutan Strategis Indonesia, 2025)
The dishwashing liquid soap-making training is a form of community empowerment activity aimed at improving skills while also creating business opportunities for the residents of Medan Krio Village in Hamlet IV. This activity is driven by the community’s need for affordable, eco-friendly, and economically valuable household products. The training process was carried out through counseling, demonstrations, and hands-on practice, enabling participants not only to gain theoretical understanding but also to be able to produce dishwashing liquid independently. The methodology applied was based on the Service-Learning model, which emphasizes practical components using an experience-based learning concept. To achieve these objectives, an assessment was conducted through action tests that demonstrated how to make dishwashing liquid soap as well as promotional strategies on social media platforms. The UINSU KKN team conducted ongoing guidance on creativity, which we implemented under the title: “Dishwashing Liquid Soap-Making and Promotion Training to Improve Household Economy in Medan Krio Village.” Thus, the dishwashing liquid soap-making training is expected to become one of the sustainable community empowerment strategies in Medan Krio Village, particularly in Hamlet IV.